2021
DOI: 10.1002/jgm.3314
|View full text |Cite
|
Sign up to set email alerts
|

LINC02288 promotes chondrocyte apoptosis and inflammation through miR‐374a‐3p targeting RTN3

Abstract: Background: Dysregulation of long non-coding RNAs (lncRNAs) is related to the occurrence of osteoarthritis (OA). In the present study, we explored the role of LINC02288 and its regulatory mechanism in OA development.Methods: GSE113825 was obtained from Gene Expression Omnibus (GEO) database and analyzed to identify the differentially expressed lncRNAs in OA. Gene enrichment analyses and Kyoto Encyclopedia of Genes and Genomes biological process analysis were performed through Metascape (http://metascape.org/gp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Manipulated overexpression of Rtn3 deteriorated ALI in mice independently, whereas downregulating Rtn3 reduced the effect of miR-7a-5p silencing on mice with ALI. Regarding the biological functions of Rtn3, a study report on osteoarthritis has offered evidence that Rtn3 augments apoptosis and inflammatory response of chondrocytes [ 16 ]. Besides, in the setting of ischemia/reperfusion injury, the abnormal elevation of Rtn3 expression is an active stimuli for cardiomyocyte apoptosis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manipulated overexpression of Rtn3 deteriorated ALI in mice independently, whereas downregulating Rtn3 reduced the effect of miR-7a-5p silencing on mice with ALI. Regarding the biological functions of Rtn3, a study report on osteoarthritis has offered evidence that Rtn3 augments apoptosis and inflammatory response of chondrocytes [ 16 ]. Besides, in the setting of ischemia/reperfusion injury, the abnormal elevation of Rtn3 expression is an active stimuli for cardiomyocyte apoptosis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of a member of Rnt, Rtn3 was found to have a potential targeting relation with miR-7a-5p online. Definitely, Fu et al have profiled the pro-inflammatory property of Rtn3 in osteoarthritis [ 16 ]. Till now, little few relevant documents have discovered the relative mechanism underlying ALI with attention on Kcnq1ot1-mediated miR-7a-5p/Rtn3 axis.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, LINC02288 expression was significantly upregulated in a rat model of OA. LINC02288 knockdown reduced IL-1β-induced apoptosis and proinflammatory cytokine production in OA chondrocytes [ 41 ]. The lncRNA LOC101928134 was highly expressed in the synovial tissue of OA rats, regulated IFNA1 expression, and inhibited the JAK/STAT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Through starbase bioinformatics database, we found that the 3′UTR of reticulon 3 (RTN3) was complementary with miR-671-5p. Fu et al demonstrated that LINC02288 promotes the apoptosis and inflammatory response of chondrocytes partly by up-regulating RTN3 via absorbing miR-374a-3p [20]. In this study, we analyzed the target relationship between RTN3 and miR-671-5p and further explored their functional association in OA pathology.…”
Section: Introductionmentioning
confidence: 90%